2012
DOI: 10.1021/nl2044106
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Nano-Oxidation Sites on the Surface of Hemoglobin Crystals Using Tip-Enhanced Raman Scattering

Abstract: Hemoglobin nanocrystals were analyzed with tip-enhanced Raman scattering (TERS), surface-enhanced resonance Raman scattering (SERRS) and conventional resonance Raman scattering (RRS) using 532 nm excitation. The extremely high spatial resolution of TERS enables selective enhancement of heme, protein, and amino acid bands from the crystal surface not observed in the SERRS or RRS spectra. Two bands appearing at 1378 and 1355 cm(-1) assigned to the ferric and ferrous oxidation state marker bands, respectively, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 36 publications
1
59
0
Order By: Relevance
“…The Raman spectra of Hb, Mb, cyt c and HRP (EC 1.11.1.7) are well known therefore, here we focus on the comparison between the most prominent bands of the Resonance Raman spectra of standard compounds measured with the use of 488 nm and 532 nm excitation wavelengths (Figs. and ).…”
Section: Resultsmentioning
confidence: 99%
“…The Raman spectra of Hb, Mb, cyt c and HRP (EC 1.11.1.7) are well known therefore, here we focus on the comparison between the most prominent bands of the Resonance Raman spectra of standard compounds measured with the use of 488 nm and 532 nm excitation wavelengths (Figs. and ).…”
Section: Resultsmentioning
confidence: 99%
“…Other bacteria-derived samples, such as isolated membrane patches from Halobacterium salinarum have also been measured with TERS, with different patches able to be distinguished [373]. Wood et al demonstrated measurement of hemozoin crystals in sectioned erythrocytes which had been infected with malaria parasites [374], and were also able to identify nano-oxidation sites with TERS [375]. [353]).…”
Section: Applicationsmentioning
confidence: 99%
“…To date, TERS has shown wide application in fields, such as surface science, 1-4 nanomaterials, 5-8 biological systems, [9][10][11][12][13] catalysis, 4, 14-16 and molecular electronics. To date, TERS has shown wide application in fields, such as surface science, 1-4 nanomaterials, 5-8 biological systems, [9][10][11][12][13] catalysis, 4, 14-16 and molecular electronics.…”
Section: Introductionmentioning
confidence: 99%